Fungicide Efficacy on Fusarium Head Blight of Hard Red Winter Wheat in Parsons, KS - Sylvia R.G. Moraes; Bruno C. Pedreira; Gretchen F. Sassenrath; Erick De Wolf; Rodrigo B. Onofre; Kelsey Andersen Onofre (Kansas Agricultural Experiment Station Research Reports, 2023)
In 2022, a field experiment was conducted to investigate the efficacy of fungicide programs on Fusarium head blight (FHB) and deoxynivalenol (DON) levels. Fungicide treatments were evaluated in plots of the hard red winter wheat cultivar ‘KanMark’ inoculated withFusarium graminearumin Parsons, KS. Treatments consisted of a single application of Prosaro, Caramba, Miravis Ace, Prosaro Pro, or Sphaerex at early anthesis (Feekes 10.5.1), or dual application of Miravis Ace at early anthesis followed by (fb) Prosaro Pro, Sphaerex, or Folicur at 4 days after early anthesis. All fungicide programs numerically reduced FHB visual symptoms and resulted in increased yield compared to the untreated check, although differences were not statistically significant in all cases. The double application treatments (Miravis AcefbProsaro Pro, and Miravis AcefbSpharex) resulted in the highest increase in test weight. Miravis Ace applied at early anthesisfbProsaro Pro applied at 4 days after early anthesis resulted in the lowest DON levels (79% less than the untreated check).
Keywords: chemical control; wheat scab; deoxynivalenol (DON); disease; field crop